Clinical and immunomorphological predictors of the adverse course of chronic hepatitis C - I. A. Karabak; D. Yu. Lobzin; V. E. Karev (Журнал инфектологии)
Wide incidence and high rate of poor outcomes of viral hepatitis C makes this issue very important. In majority of cases viral hepatitis C develops chronic form of the disease resulting in fibrosis, cirrhosis and hepatocellular carcinoma in longstanding period of time. The specificity of clinical presentation and particular aspects of pathogenesis complicates making the prognosis of its course significantly.Objective. Estimation of clinical and immunomorphological factors that influence the process of fibrogenesis in chronic hepatitis C.Material and methods. The object of our research was 64 liver biopsy samples from adults with natural course of chronic hepatitis C. Using immunohistochemistry and morphometric method intrahepatic CD3+, CD8+Т-lymphocites, CD68+-macrophages, alfa-SMA+-stellate cells were counted. Then the connection between this markers and histological activity index (HAI), stage of fibrosis, ALT elevation, viral load and viral genotype were evaluated.Results. It was established, that increasing amount of intrahepatic CD8+-lymphocytes implicates augmentation of histological activity and ALT level: CD8 abs./HAI – r=0,56; CD8 abs/ALT – r=0,45; HAI/ALT – r=0,58 (p<0,05), and also raising of CD68+-macrophages in mild and moderate HAI: СD8 абс./СD68 абс. – r=0,58 и 0,54 accordingly (p<0,05), and alfa-SMA+-stellate cells. Histological activity was prone to raise with the stage of fibrosis. Also the higher number of intrahepatic CD8+-lymphocytes, HAI and ALT elevation was identified in cases with viral genotype 3.Conclusion. As a result, unfavorable implication of cellrelated  immune lesion and viral genotype 3 in fibrosis progression was  demonstrated. The role of viral load was ambiguous.